Lower Limb Muscle Activation Adaptation During Single and Dual Walking Tasks in Healthy Young Adults (International Journal of Physiotherapy, 2021)
Background: Falls due to altered balance is a worldwide health concern. Previous investigations have delved into the effect of dual-tasking balance and gait (kinematic alteration) because of the increased attentional loads demanded from the brain. In addition, impaired neuromuscular patterns could additionally contribute to gait alterations and increased fall risk. This study aims to identify the muscle activation pattern of lower limb musculature during single and dual tasks in healthy young adults.Methods: Thirty-four participants (9 males and 25 females, mean age of 24.88 ± 5.13) completed two 7-meter level ground walk trials under singular then dual tasks. We implemented an amplitude analysis filter to normalize EMG amplitude data to obtain a percentage of the amplitude (0-100%) and timing amplitude.Results: The ANOVA analysis revealed no considerable distinction in muscle activity amplitude among dual and single cognitive tasks (p ≥ 0.05). When assessing the activation pattern while walking on an even surface, Gluteus maximum (GMAX) and gastrocnemius (GA) exhibited similar timing patterns associated with gluteus medius (p = 0.01) and tibialis anterior (p = 0.001)., GMAX showed greater average amplitude contrasted to most of the research musculature.Conclusion: Our investigation identified similarities in lower extremity muscle activity patterns among single and dual tasks in healthy young adults. This study ushers in recognizing distinct muscle activation patterns among lower extremity musculature. Clinicians should consider activation of lower limb extensor musculature during gait training, prioritizing GMAX, GA, and Gluteus Medius weakness contributing to impaired gait mechanics to minimize gait imbalances regarding muscle activity.